PERBEDAAN EFEKTIFITAS TEHNIK RENDAM KAKI AIR HANGAT DAN TEHNIK SLOW DEEP BREATH TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI POSYANDU LANSIA DAHLIA ARJASA JEMBER - Zahruddin; Muhammad Amin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Hypertension is a non-communicable disease which is the main concern in the world. WHO in 2012 stated that the incidence of hypertension reached 50% of the total population in the world. The Ministry of Health of the Republic of Indonesia in 2013 stated that there was an increase in the prevalence of hypertension in Indonesia starting from 7.6% in 2007 to 9.5% in 2013. One of the factors that cause hypertension is age so that hypertension is often found in the elderly. Measures to overcome hypertension can use pharmacological therapy and non-pharmacological therapy. Pharmacological therapy in addition to providing therapeutic effects can also provide side effects that can harm the body while non-pharmacological therapies do not provide side effects on the body. Non-pharmacological therapies include slow deep breath and warm feet soak. This study aims to determine the differences in the effectiveness of the warm water foot soak technique and the Slow Deep Breath technique to reduce blood pressure in the elderly with hypertension in the elderly Dahlia Arjasa Jember. The design of this study used a quasi experimental design with the Nonequivalent Control Group Design approach, there were 2 groups, a group treated with SDB and a group treated with warm water foot baths. The population in this study were 20 populations who have high blood pressure (hypertension) in the elderly Posyandu Dahlia Arjasa Jember and a sample of 20 respondents with sampling techniques using simple random sampling. The results of this study indicate that there is a difference in the effectiveness of SDB technique and warm water foot bath technique with the results of bivariate analysis with mannwhitney test obtained p value systole after SDB treatment and foot bath water warm up to 0.017 (<0.05) and p value diastole after treatment SDB and warm water foot bath was 0.001 (<0.05) where from the mean of the two treatments it was found that warm foot bath water was more effective in lowering blood pressure